Religion, Ethnicity, and Race in Finnish Legal Cases on Insults against Religion - Tuomas Äystö (FINNISH SOC STUDY RELIGION, 2022)
This article examines religious insults and related legal practice in Finland during the 21st century. It investigates how the Office of the Prosecutor General, the courts, and defendants construct the category of religion - which is the object of special protection - and how discourses on ethnicity and race play a role in this process. It is found that the language of both officials and defendants is affected by the lay discourse in Finnish society. This includes the decline of the importance of the formal category of religion found in the letter of the law and the increasing importance of the popular category. It is also argued that while being part of the established religion discourse improves the chances of benefiting from religious insult legislation, the said law is found to be a relatively ineffective avenue for groups seeking justice in the context of speech or actions considered religiously offensive. More generally, the article demonstrates that the discursive study of religion can benefit from a perspective in which categories such as ethnicity and race, which often intersect with the category of religion in social practice, are incorporated into the analysis.